2017
DOI: 10.1111/anae.13998
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, controlled trial of rectus sheath bupivacaine and intrathecal bupivacaine, without or with intrathecal morphine, vs. intrathecal bupivacaine and morphine after caesarean section

Abstract: We recruited 144 women of whom 131 underwent scheduled caesarean section and were allocated to intrathecal bupivacaine without (46) or with (47) morphine and postoperative rectus sheath bupivacaine; or intrathecal bupivacaine with morphine and postoperative rectus sheath saline (38). We measured postoperative pain with a 10-point numeric rating scale. The mean (SD) areas under the curve for pain on movement during 48 postoperative hours were 273.5 (63.6), 223.8 (80.7) and 223.8 (80.7), respectively, p = 0.008.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…A urological study suggested that multimodal pain control via intrathecal bupivacaine/morphine may optimally improve the quality of early recovery and reduce postoperative pain, being associated with less pain during exertion and fewer bladder spasms (compared to a control group) [5]. Our ITMB block data are similar to those of previous laparoscopic or open surgery reports [5,[14][15][16]; the ITMB block was a feasible and practicable form of pain relief, not associated with serious complications (such as nerve injury) during or after surgery, and was better than the RSB or IV-PCA alone.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A urological study suggested that multimodal pain control via intrathecal bupivacaine/morphine may optimally improve the quality of early recovery and reduce postoperative pain, being associated with less pain during exertion and fewer bladder spasms (compared to a control group) [5]. Our ITMB block data are similar to those of previous laparoscopic or open surgery reports [5,[14][15][16]; the ITMB block was a feasible and practicable form of pain relief, not associated with serious complications (such as nerve injury) during or after surgery, and was better than the RSB or IV-PCA alone.…”
Section: Discussionsupporting
confidence: 75%
“…In an orthopedic study, intrathecal morphine seemed to be more reliable in terms of analgesic e cacy and opioid-sparing than a femoral nerve block [15]. In a gynecological study, the addition of intrathecal bupivacaine to intrathecal morphine signi cantly improved postoperative pain relief, but the addition of rectus sheath bupivacaine to intrathecal morphine did not afford additional analgesia [16]. A urological study suggested that multimodal pain control via intrathecal bupivacaine/morphine may optimally improve the quality of early recovery and reduce postoperative pain, being associated with less pain during exertion and fewer bladder spasms (compared to a control group) [5].…”
Section: Discussionmentioning
confidence: 98%
“…NRS scores for global health and pain scores, although quick to measure, do not provide a holistic indication of patient-reported functional recovery. 6,7 To develop an obstetric-specific QoR score, we started with a broad selection of recovery items, and then evaluated and refined the tool in five stages. ObsQoR-11 contains no items from the 'psychological support' domain, which could imply that recovery factors relating to self-efficacy and functional ability are more important for CD-related health than the perceived support from staff or relatives during hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Anaesthetic capacity is extremely limited in Uganda, with currently approximately 70 physician anaesthetists and 430 non‐physician anaesthetists serving a population of almost 40 million . The field of anaesthesia encompasses not simply the delivery of intra‐operative anaesthesia but also pain control, critical care and improvement of peri‐operative safety . The use of ultrasound‐guided regional anaesthesia may both stimulate professional development, and allow anaesthetists to engage with their surgical and nursing colleagues to promote analgesia beyond the operating room.…”
Section: Discussionmentioning
confidence: 99%